2013
DOI: 10.1111/jan.12174
|View full text |Cite
|
Sign up to set email alerts
|

An integrative literature review on preparing nursing students through simulation to recognize and respond to the deteriorating patient

Abstract: Simulation exposes students to a broader range of experiences whilst in a safe environment with transference of skills to clinical practice occurring. Confidence, clinical judgement, knowledge and competence, all vital in the care of a deteriorating patient, were enhanced. However, evidence of simulation used specifically to prepare nursing students to recognize and respond to the deteriorating patient appeared limited. This educational field appears rich for interprofessional collaboration and further researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 35 publications
2
51
0
5
Order By: Relevance
“…What was not clear in this integrative review was the amount and type of education that ward nurses felt helped them to recognize patient deterioration. Increasingly, deliberate practice in the form of simulation has been gaining popularity in the undergraduate and postgraduate nursing curriculum (Fisher & King , Hart et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…What was not clear in this integrative review was the amount and type of education that ward nurses felt helped them to recognize patient deterioration. Increasingly, deliberate practice in the form of simulation has been gaining popularity in the undergraduate and postgraduate nursing curriculum (Fisher & King , Hart et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that individuals' self-confidence is a predictor of their ability to perform effectively in new situations. [13][14][15] Moreover, a person's belief in his or her self-confidence varies according to the 1) difficulty of the task, 2) certainty in performing a task at a given level of difficulty, and 3) extent to which the difficulty of the task generalizes across situations. [14] Because nursing is a contextually situated practice, an individual's competence in any given clinical situation is derived from building a repertoire of experiences to inform clinical decision making.…”
Section: Simulationmentioning
confidence: 99%
“…The post-test scores increased across the scenarios from Myocardial infarction and cardiac arrest, Shock and trauma to the DKA and hyperglycaemia compared to the videos. Higher performance among intensive care nurses in simulated emergency scenarios [36] and increased critical thinking, clinical judgement, skill acquisition, clinical reasoning [37][38][39]. Simulation translated application in knowledge [40,41] with use of clinical scenarios [42].…”
Section: Resultsmentioning
confidence: 99%